Evaluating the Effects of Covalency on Anti-Tumour Immune Function Using Syngeneic Tumour Models - Raajkumar, Akshaya (My University, 2022)
Synthetic immunology aims to utilize synthetic chemistry and molecules to modulate natural immunological functions against cancer cells. Synthetic molecules developed for use in immunotherapy are antibody recruiting molecules (ARMs) that can utilize antibodies in human serum as a weapon against cancer cells. The development of ARMs has inspired the creation of a novel class of synthetic immunotherapeutics - covalent antibody recruiting molecules (cARMs). cARMs not only bind but covalently label specific antibodies to recruit them to the tumour cell surface. First generation cARM molecules consist of a human prostate specific membrane antigen (hPSMA) target binding domain, an antibody labeling acyl imidazole ester domain, and an anti-dinitrophenyl (DNP) antibody binding domain. The ALD domain instigates an irreversible covalent bond to label anti-DNP antibodies which enables the generation of a tumour therapeutic antibody directly in vivo which can enact immune cell function against tumour cells. cARMs have been proven to recruit anti-DNP antibodies to hPSMA expressing cells and mediate selective antibody-dependent cellular phagocytosis/cytotoxicity (ADCP/ADCC) against cancer cells in in vitro assays. Following the development of a mouse model, initial in vivo studies demonstrated significantly improved survival in tumour bearing mice that were treated with ARM and cARM. In vivo labeling studies displayed successful labeling of anti-DNP antibodies in circulation by cARMs and the presence of labeled antibodies for at least 72hrs in circulation. Conversely, ARM mediated antibody binding was considerably less at all examined time points. Resolving autoinhibition limitations of cARMs allowed for enhanced and improved labeling of anti-DNP antibodies both in vitro and in vivo. This enhancement in labeling could allow for improved ternary and immune active quaternary complex formation to mediate tumour cell death. In vivo tumour studies demonstrated increased survival in tumour bearing mice treated with non-autoinhibited cARM when compared to ARM. Furthermore, innate immune cell populations were shown to increase in peripheral blood of tumour bearing mice treated with ARM and cARM. While cARM treatment dosing and concentration are yet to be optimized, this thesis demonstrates the potential of cARMs as an immunotherapeutic. cARMs can be synthesized to target a variety of cancer cell specific antigens, selectively label antibodies, and has the potential to recruit multi-specific therapeutic antibodies against heterogeneous tumours.
Keywords: Immunology; Chemical biology